Primary herpetic gingivostomatitis pada individu dewasa muda Primary herpetic gingivostomatitis in young adult - Erni Marlina; Hadi Soenartyo (DiscoverSys Inc., 2012)
Primary herpetic gingivostomatitis (PHGS) is a disease of primary infection with herpes simplex virus type I, which isoften infects children and late adolescents. However, the disease could affect adults, too. This report aims to discussthe diagnosis and treatment of a young adult suffered PHGS which is previously diagnosed as pericoronitis. A patient,24-year-old man, working in the private sector, complained of pain on the gingiva at the posterior wisdom mandibularteeth, accompanied with pain on pharyng and labium ulceration that did not heal even the patient took drugs frompublic health centre. Patient was prescribed acyclovir 200 mg 5 times a day, mouthwash containing anasteticum,systemic analgesics, and vitamins. The ulceration healed 2 days later. It was concluded that despite PHGS occurscommonly in children, but the adult could suffer this disease, and detailed anamnesis along with intraoral andextraoral examination are the main key for accurate diagnosis and therapy.